Neogenin as a receptor for early cell fate determination in preimplantation mouse embryos. - Jae Ho Lee; Sung Sook Choi; Hae-Won Kim; Wen Cheng Xiong; Churl K Min; Sang Jin Lee (PLoS ONE, 2014)
The first cell lineage determination in embryos takes place when two cell populations are set apart, each differentiating into the trophectoderm (TE) and inner cell mass (ICM), respectively. It is widely believed that position/polarity cues play a key role in triggering this differentiation, but it remains unclear how extracellular cues are transduced into cell fate determination. Here, we provide evidence that supports that neogenin is implicated in relaying extracellular cues into the first cell fate determination in preimplantation mouse embryos. A polarized and transient distribution of neogenin was manifested in early blastomeres. Neogenin up-regulation by its overexpression accelerated ICM development in the blastocyst concomitant with the activation of the ICM-specific transcription factors Oct3/4, Sox2, and Nanog while its depletion by small hairpin RNAs (shRNAs) caused a developmental abnormality of poorly endowed ICM accompanied by the deactivation of Oct3/4, Sox2, and Nanog. Treatment with netrin-1 among neogenin ligands further impaired both embryonic development and ICM formation while repulsive guidance molecule c (RGMc) led to opposite consequences, enhancing ICM formation. From this study, we propose a model whereby neogenin interprets its own expression level to control the first cell fate determination in response to extracellular cues.